Valuasi Ekonomi dan Efisiensi Pemanfaatan Sumber Daya Air Multi-Sektor di Mata Air Baumata - Laurentius DW Wardhana; Elisabeth Afjun Teme; Aah Ahmad Almulqu; Flora Evalina Ina Kleruk; Meilyn R Pathibang; Dwi Wahyuni (MAKILA, 2026)
Water resources play a crucial role in supporting socio-economic activities, particularly in semi-arid regions characterized by limited and uneven water availability. Increasing pressure on water resources requires a comprehensive understanding of utilization patterns and economic value across sectors. This study aims to analyze water use, estimate its economic value, and evaluate the efficiency of water utilization across multiple sectors at Baumata Spring, East Nusa Tenggara. A quantitative approach was applied using a hybrid economic valuation method combining the Market Price Method (MPM), cost-based approach, and production-based approach. The results show that total water utilization reached 4,554,058 m³/year, dominated by the agricultural sector (90.40%). The total economic value amounted to IDR 2.46 billion per year, with the largest contributions coming from domestic and bottled water industry sectors, while agriculture contributed relatively little despite consuming most of the water. Efficiency analysis reveals significant disparities among sectors, ranging from IDR 5.01/m³ to IDR 1,214,486/m³. These findings indicate that the economic value of water is not solely determined by the volume of use, but by each sector’s capacity to generate added value. Therefore, water resource management should be oriented toward optimizing allocation based on efficiency and economic value while considering social equity and food security.